Impact of BAFF Blockade on Inflammation, Germinal Center Reaction and Effector B-Cells During Acute SIV Infection - Borhis, Gwenoline; Trovato, Maria; Ibrahim, Hany M.; Isnard, Stephane; Le Grand, Roger; Bosquet, Nathalie; Richard, Yolande (Frontiers in Immunology, 2020)
Memory B-cell dysfunctions and inefficient antibody response suggest germinal center (GC) impairments during HIV/SIV infection with possible contribution of overproduced B-cell activating factor (BAFF). To address this question, we compared proportions and functions of various B-cell subsets and follicular helper T-cells (TFH) in untreated (Placebo) and BR3-Fc treated (Treated) SIV-infected macaques. From day-2 post-infection (dpi), Treated macaques received one weekly injection of BR3-Fc molecule, a soluble BAFF antagonist, for 4 weeks. Whereas the kinetics of CD4+ T-cell loss and plasma viral loads were comparable in both groups, BAFF blockade delayed the peak of inflammatory cytokines (CXCL10, IFN), impaired the renewal of plasmacytoid dendritic cells and fostered the decline of plasma CXCL13 titers after 14dpi. In Treated macaques, proportions of total and naïve B-cells were reduced in blood and spleen whereas SIV-induced loss of marginal zone (MZ) B-cells was only accentuated in blood and terminal ileum. Proportions of spleen GC B-cells and TFH were similar in both groups, with CD8+ T-cells and rare Foxp3+ being present in spleen GC. Regardless of treatment, sorted TFH produced similar levels of IL21, CXCL13 and IFN but no IL2, IL4 or BAFF and exhibited similar capacities to support IgG production by autologous or heterologous B-cells. Consistently, most TFH were negative for BAFF-R and TACI. Higher proportions of resting and atypical (CD21lo) memory B-cells were present in Treated macaques compared to Placebo. In both groups, we found higher levels of BAFF-R expression on MZ and resting memory B-cells but low levels on atypical memory B-cells. TACI was present on 20-30% of MZ, resting and atypical memory B-cells in Placebo macaques. BAFF blockade decreased TACI expression on these B-cell subsets as well as titers of SIV-specific and vaccine-specific antibodies arguing for BAFF being mandatory for plasma cell survival. Irrespective of treatment, GC B-cells expressed BAFF-R at low level and were negative for TACI. In addition to key information on spleen BAFF-R and TACI expression, our data argue for BAFF contributing to the GC reaction in terminal ileum but being dispensable for the generation of atypical memory B-cells and GC reaction in spleen during T-dependent response against SIV.